Diseño De Un Sistema De Inteligencia De Negocio Para La Empresa B Y O Ingeniería Y Calidad Ubicada En La Ciudad De Armenia (2016)
This project aims to design an intelligence system of busineess for “B y O Ingeniería y Calidad” enterprise. It will complement the Datamarts that correspond to areas such as: technical laboratory, staff, equipment and accounting that give support to the process of making decisions and executing reports by the management. The process portrays an useful tool whose priority is to facilitate the understanding and the show of information that has to do with the processes for the management of data results of trials, customers, equipment and involved staff. For the development of this project it was choosen as methodological component the one proposed in the degree work “Marco de Trabajo para Implementar Datamarts en la Universidad del Quindío” which defines and takes a sort of resources and supports based on the Kimball methodology for the development of intelligence systems of business.